The Effect of Liquidity and Solvability on Stock Price Through Profitability - Sofyaun, Ashari; Setijoadi, Setijoadi; Lestari, Winda (Universitas Syiah Kuala, 2025)
This study aims to examine the effect of liquidity, measured by the Quick Ratio (QR) and Current Ratio (CR), and solvency, measured by the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), on stock prices through profitability as a mediating variable, which is measured by the Return on Asset Ratio (ROA) and Return on Equity Ratio (ROE). The data used in this research is secondary data obtained from Annual Reports. The sample consists of nine telecommunications subsector companies listed on the Indonesia Stock Exchange that meet the research criteria, covering the period from 2019 to 2023 (five years), resulting in 45 observations. This study utilizes SmartPLS 3 as the analytical tool and employs a quantitative research method. The findings of this study indicate that liquidity has a positive and significant effect on profitability. Solvency has no effect on profitability or stock prices. Liquidity does not effect stock prices. Profitability does not effect stock prices. Furthermore, liquidity does not effect stock prices through profitability, and solvency does not effect stock prices through profitability.